Unveiling the resilience mechanism: Strigolactones as master regulators of plant responses to abiotic stresses - Muhammad Fasih, Khalid (2024)
Strigolactones (SLs) are an emerging class of plant hormones that play important roles in plant growth, development, and response to environmental stresses. This review summarizes recent findings on the roles of SLs in mitigating heat, drought, and salinity stresses in plants. Under high temperatures, SLs help maintain photosynthesis, antioxidant activity, and expression of heat shock proteins to confer thermotolerance. During drought, SLs regulate stomatal closure and promote root growth and mycorrhizal associations to enhance water uptake and retention. SLs also modulate ion homeostasis and antioxidant systems under salinity stress. On the physiological level, exogenous SL can increase chlorophyll content, photosynthetic efficiency, proline accumulation, and activity of antioxidant enzymes like SOD, POD, and CAT across plant species. On the molecular level, SLs regulate genes involved in the cell cycle, heat shock proteins, hormone signaling (auxin, ABA, ethylene), and SL biosynthesis and signaling components like MAX1-4, D14, and D53. Overall, SLs are emerging as promising plant growth regulators that can potentially be applied exogenously to improve abiotic stress tolerance in crops through coordinated molecular, biochemical, and physiological responses. More studies are needed to fully elucidate SL signaling cascades in different plant species and environments.